Roles of salivary components in Streptococcus mutans colonization in a new animal model using NOD/SCID.e2f1-/- mice. - Tatsuro Ito (PLoS ONE, 2012)
Streptococcus mutans plays an important role in biofilm formation on the tooth surface and is the primary causative agent of dental caries. The binding of S. mutans to the salivary pellicle is of considerable etiologic significance and is important in biofilm development. Recently, we produced NOD/SCID.e2f1(-/-) mice that show hyposalivation, lower salivary antibody, and an extended life span compared to the parent strain: NOD.e2f1(-/-). In this study we used NOD/SCID.e2f1(-/-) 4 or 6 mice to determine the roles of several salivary components in S. mutans colonization in vivo. S. mutans colonization in NOD/SCID.e2f1(-/-) mice was significantly increased when mice were pre-treated with human saliva or commercial salivary components. Interestingly, pre-treatment with secretory IgA (sIgA) at physiological concentrations promoted significant colonization of S. mutans compared with sIgA at higher concentrations, or with human saliva or other components. Our data suggest the principal effects of specific sIgA on S. mutans occur during S. mutans colonization, where the appropriate concentration of specific sIgA may serve as an anti-microbial agent, agglutinin, or an adherence receptor to surface antigens. Further, specific sIgA supported biofilm formation when the mice were supplied 1% sucrose water and a non-sucrose diet. The data suggests that there are multiple effects exerted by sIgA in S. mutans colonization, with synergistic effects evident under the condition of sIgA and limited nutrients on colonization in NOD/SCID.e2f1(-/-) mice. This is a new animal model that can be used to assess prevention methods for dental biofilm-dependent diseases such as dental caries.